1996
DOI: 10.1016/s0166-4328(96)00052-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent plasticity in visual forebrain areas of the zebra finch

Abstract: It has previously been shown that the activity of some areas of the forebrain of birds is dependent on the arousal level of the animal. Other areas do not show this dependency. This paper, on the basis of 2-DG experiments and spine density measurements on Golgi-impregnated tissue, shows that primary telencephalic target areas of the two visual pathways of zebra finch males are not dependent on arousal for activation. In contrast, secondary areas of both visual pathways show arousal-dependent activation. Only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Such discrepancies in identical behavioral testing paradigms have also been shown by others (Duncan et al, 1993;Tlemçani et al, 2000), and the two methods could supplement each other (Sharp and Sagar, 1992). Studies in our laboratory have shown that the primary visual areas, ectostriatum and intercalated nucleus of hyperstriatum accessorium (IHA) that depict enhanced 2-DG accumulation, do not express fos (Sadananda and Bischof, 2001) and do not show morphological changes in synaptic connectivity (Rollenhagen and Bischof, 1996) on consolidation of sexual imprinting, whereas secondary visual areas HAD and LNH do.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such discrepancies in identical behavioral testing paradigms have also been shown by others (Duncan et al, 1993;Tlemçani et al, 2000), and the two methods could supplement each other (Sharp and Sagar, 1992). Studies in our laboratory have shown that the primary visual areas, ectostriatum and intercalated nucleus of hyperstriatum accessorium (IHA) that depict enhanced 2-DG accumulation, do not express fos (Sadananda and Bischof, 2001) and do not show morphological changes in synaptic connectivity (Rollenhagen and Bischof, 1996) on consolidation of sexual imprinting, whereas secondary visual areas HAD and LNH do.…”
Section: Discussionsupporting
confidence: 54%
“…These areas, which depict enhanced accumulation of 2-DG (Bischof and Hermann, 1986), fos expression after chasing and first courtship (Sadananda and Bischof, 2002), and changes in spine densities with changing social contexts (Rollenhagen and Bischof, 1996), are probably affected by exposure to the imprinting stimulus. Both are innervated by the hippocampus (Casini et al, 1986;Székely and Krebs, 1996), and parts of both project to the LNH (Sadananda and Bischof, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ZENK protein levels at any given time could represent an integration of the animal's activity resulting from its wakefulness or arousal state, as described in Cirelli et al (1996). Interestingly, activity in HA and HD, as revealed by 2-deoxyglucose uptake, is known to be modulated by arousal (Bischof and Herrmann, 1986;Rollenhagen and Bischof, 1996). 2) ZENK protein expression in nuclei of the anterior forebrain pathway (area X and lMAN) related to singing was quite variable, indicating the influence of an unidentified factor.…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence that social experience and learning leads to dramatic rearrangements of neuronal connectivities has also been found in other avian species. In zebra finches arousal, different rearing conditions and social experience induced significant changes of neuronal morphology in the MNH and in the so called archi‐neostriatum caudale ( Rollenhagen & Bischof 1991; Rollenhagen & Bischof 1994), whereas no changes were found in the ectostriatum ( Rollenhagen & Bischof 1996). Song or speech learning, another juvenile learning process, induces a 41% decrease of spine density in the lateral part of the magnocellular nucleus of the anterior neostriatum of male zebra finches ( Wallhäusser‐Franke et al .…”
Section: Discussionmentioning
confidence: 99%